1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
b[n]=b[1]*q^(n-1)
b[1]=-1/27
b[2]=b[1]*q
b[2]=-1/27q
b[3]=b[1]q^2
b[3]=-1/27q^2
b[4]=b[1]q^3
b[4]=-1/27q^3
b[5]=b[1]q^4
b[5]=-1/27q^4
b[1] *b[2]*b[3]*b[4]*b[5]=-1/243
-1/27*(-1/27)q*(-1/27)q^2*(-1/27)q^3*(-1/27)q^4=-1/243
(-1/27)^5 *q^(1+2+3+4)=-1/243
((-1/3)^3)^5*q^10=(-1/3)^5
(-1/27)^5*(q^2)^5=(-1/3)^5
(-1/27q^2)^5=(-1/3)^5
-1/27q^2=-1/3
q^2=-1/3*(-27)
q^2=9
q<0
q=-3